The impact of TiO2 nanoparticle exposure on transmembrane cholesterol transport and enhanced bacterial infectivity in HeLa cells. (November 2021) - Yang, Fan; Liu, Shu-Lin; Xu, Yan; Walker, Stephen G.; Cho, Wonhwa; Mironava, Tatsiana; Rafailovich, Miriam
Abstract: We have previously shown that exposure to TiO2 nanoparticles (NPs) reduces the resistance of HeLa cells to bacterial infection. Here we demonstrate that the increased infectivity is associated with enhanced asymmetry in the cholesterol distribution. We applied a live cell imaging method which uses tunable orthogonal cholesterol sensors to visualize and quantify in-situ cholesterol distribution between the two leaflets of the plasma membrane (PM). In the control culture, we found marked transbilayer asymmetry of cholesterol, with the concentration in the outer plasma membrane (OPM) being 13 ± 2-fold higher than that in the inner plasma membrane (IPM). Exposure of the culture to 0.1 mg/mL of rutile TiO2 NPs increased the asymmetry such that the concentration in the OPM was 51 ± 10 times higher, while the total cholesterol content increased only 21 ± 2%. This change in cholesterol gradient may explain the increase in bacterial infectivity in HeLa cells exposed to TiO2 NPs since many pathogens, including Staphylococcus aureus used in the present study, require cholesterol for proper membrane attachment and virulence. RT-PCR indicated that exposure to TiO2 was responsible for upregulation of the ABCA1 and ABCG1 mRNAs, which are responsible for the production of the cholesterol transporter proteins that facilitate cholesterol transport across cellular membranes. This was confirmed by the observation of an overall decrease in bacterial infection in ABCA1 knockout or methyl-β-cyclodextrin-treated HeLa cells, as regardless of TiO2 NP exposure. Hence rather than preventing bacterial infection, TiO2 nanoparticles upregulate genes associated with membrane cholesterol production and distribution, hence increasing infectivity. Statement of significance: A great deal of work has been done regarding the toxicology of the particles, especially focusing on detrimental outcomes associated with reactive oxygen species (ROS) production. In this paper we show unambiguously a very surprising result, namely the ability of these particles to enhance bacterial infection even at very small exposure levels, where none of the deleterious effects of ROS products can yet be detected. Using a new imaging technique, we are able to demonstrate, in operando, the effect of the particles on cholesterol generation and distribution in live HeLa cells. This paper also represents the first in a series where we explore other consequences of increased membrane cholesterol, due to particle exposure, which are known to have multiple other consequences on human tissue function and development. Graphical abstracts: Image, graphical abstract